Journey of candidates who were unmatched in the Canadian Residency Matching Service (CaRMS): A phenomenological study (Canadian Medical Education Journal, 2020)
Background: Each year, a number of medical students are unmatched in the Canadian Residency Matching Service (CaRMs) match. There is little information on the experiences of unmatched candidates. This study seeks to explore the experiences of applicants who were unmatched in the first iteration of their CaRMS applicationsMethods: We interviewed 15 participants who were previously unmatched, using a semi-structured interview guide to ask them of their experiences on the following domains: the overall unmatched experience; circumstances leading to their unmatched status; resources employed; barriers experienced; recommendations; and, their eventual career outcomes. We independently identified major themes from field notes to code the data using a phenomenology approach.Results: Our participants universally reported negative emotions, concerns regarding privacy and confidentiality breaches, and stigma faced (real or perceived). Systemic challenges included: lack of information, pressures faced from undergraduate medical education, and logistical issues such as financial challenges, licensing and scheduling issues. The utility of peer support differed for individual participants, but all those who had support from other unmatched candidates felt that to be useful.Conclusions: Our participants reported significant challenges faced after being unmatched. Based on these experiences, we identified four major recommendations to support candidates through their unmatched journey.